2019
DOI: 10.1016/j.molcel.2019.01.043
|View full text |Cite
|
Sign up to set email alerts
|

The Ribosome Cooperates with a Chaperone to Guide Multi-domain Protein Folding

Abstract: Highlights d How the ribosome modulates nascent chain folding switches during elongation d Sequential domain-wise folding reduces misfolding d Co-translational folding can be reversed by an unexpected unfolding pathway d Protection of folded domains is an unanticipated chaperone function

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
130
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(139 citation statements)
references
References 58 publications
(83 reference statements)
7
130
2
Order By: Relevance
“…In contrast to the translation rate-sensitive effects we observed for CAT folding, recent in vitro single molecule force-unfolding experiments have shown that some small, ribosome-bound natively-folded domains can fold via similar mechanisms on and off the ribosome (69,70). However, as these studies noted, forced unfolding measured by molecular tweezers cannot capture the transient folding of a nascent chain during its synthesis (33), and hence what is measured in these experiments is the effect of close proximity of the ribosome surface, rather than co-translational folding. The very robust folding behavior of these wellcharacterized, reversible folding models may indeed lead to indistinguishable folding behavior during translation, a model supported by recent force-feedback folding measurements (71).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…In contrast to the translation rate-sensitive effects we observed for CAT folding, recent in vitro single molecule force-unfolding experiments have shown that some small, ribosome-bound natively-folded domains can fold via similar mechanisms on and off the ribosome (69,70). However, as these studies noted, forced unfolding measured by molecular tweezers cannot capture the transient folding of a nascent chain during its synthesis (33), and hence what is measured in these experiments is the effect of close proximity of the ribosome surface, rather than co-translational folding. The very robust folding behavior of these wellcharacterized, reversible folding models may indeed lead to indistinguishable folding behavior during translation, a model supported by recent force-feedback folding measurements (71).…”
Section: Discussioncontrasting
confidence: 59%
“…This suggests that (i) the conformations adopted early during the folding process are crucial to successful folding and (ii) the cellular environment supports the formation of early folding intermediates that are distinct from the conformations populated upon dilution from denaturant. Indeed, there is substantial evidence that molecular chaperones are crucial to the successful folding of many complex proteins in vivo (29)(30)(31)(32)(33). Although it has been hypothesized that synonymous codon changes could alter elongation rate and modify folding mechanisms in vivo, it has thus far been challenging to find evidence to support this hypothesis from experiments performed in vivo, possibly due to buffering provided by molecular chaperones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribosomes are nano-machines that translate information coded in a messenger RNA into proteins in all living organisms. Recently, it has been found that ribosomes can also play a significant role in the process of co-translational folding by modulating the folding of a nascent chain (NC) during translation (Kaiser et al, 2011;Cabrita et al, 2016;Javed et al, 2017;Samulson et al, 2018;Liu et al, 2019). Nascent chains (NC) can begin to acquire secondary structural elements in a cotranslational manner during emergence via the ribosome exit tunnel within the large subunit of the ribosome (Netzer W. et al, 1997;Thommen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In order to immobilize mDHFR on polystyrene beads for optical tweezers experiments, we modified the biotinylated, ybbR-tagged protein with a CoA-modified double-stranded DNA (dsOligo-CoA) that also contained a "sticky end" for ligation in an Sfp-mediated reaction 58 . After the reaction, the sample was centrifuged briefly (10 min, 16,000g, 4°C) and loaded onto a Superdex 200 column (GE Healthcare) to remove Sfp and unreacted dsOligo-CoA.…”
Section: Derivitization Of Mdhfrmentioning
confidence: 99%